2015
DOI: 10.1007/s10763-015-9621-x
|View full text |Cite
|
Sign up to set email alerts
|

‘I Hate Maths: Why Do We Need to Do Maths?’ Using iPad Video Diaries to Investigate Attitudes and Emotions Towards Mathematics in Year 3 and Year 6 Students

Abstract: Accessing children's feelings and attitudes towards mathematics is a challenging proposition since methods for data collection may be fraught in terms of bias and power relations. This article explores a method of collecting information from young students about their attitudes towards mathematics using iPads, and a video diary technique not dissimilar to the 'Big Brother' room, with which many children are familiar. We describe the development of the tool and process when implemented in a primary school setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 19 publications
0
50
0
2
Order By: Relevance
“…Educators have long been concerned with a steady decline in students attitude towards mathematics (Larkin & Jorgenson, 2016). Research has previously found that towards the end of primary school, expressions of boredom from children in mathematics are indicative of lack of stimulation, lack of challenge and a lack of direction over learning (Bibby, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Educators have long been concerned with a steady decline in students attitude towards mathematics (Larkin & Jorgenson, 2016). Research has previously found that towards the end of primary school, expressions of boredom from children in mathematics are indicative of lack of stimulation, lack of challenge and a lack of direction over learning (Bibby, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there was still less significant improvement in students' conceptual understanding. This is correlated to Oliver et al (2017), Liu & Fang (2016), Larkin & Jorgensen (2016) and Waldrip & Prain (2012) that students' misconceptions can be strong and be challenging on the way to truthful.…”
Section: Figure 6 the Graph For Students' Scores At Pre-test And Posmentioning
confidence: 89%
“…Studying students' conceptual misunderstandings can be a strong and challenging way to the solution (e.g. Oliver et al, 2017;Liu & Fang, 2016;Larkin & Jorgensen, 2016;Waldrip & Prain, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As classroom practices have an influence on students' attitudes towards mathematics, positive pedagogical practices are required to combat negative attitudes (Hubbard 2001;Larkin and Jorgensen 2015;Swars et al 2007). Thus, the potential to positively transform students' attitudes about mathematics is possible if students experience 'joy and excitement' instead of 'panic, boredom and frustration' in the classroom (Grootenboer and Marshman 2016, p. 21).…”
Section: Concluding Remarks and Implications For Future Researchmentioning
confidence: 99%